Bridging Language Education’s Theory–Practice Divide: The Interplay of Theoretical and Practical Approaches in Language Learning - Sedighe Zamani Roodsari; Jamie Harrison (Scientia Publica Media, 2026)
There have always been discussions about the interplay and persistent gap between theoretical and practical knowledge in teacher training. Although both educational research and practical application are essential, more subjective learning experiences are required to allow teachers to connect theory with practice in meaningful ways. For several decades, scholars in the field of teacher education have suggested integrating approaches to support research from an insider perspective on the effects of teaching strategies and theories. Yet, the existing theories that have traditionally framed the relationship between theory and practice do not fully assist teachers in developing practical education in real-world situations, and there is still a gap between theory and practice. Inspired by the constructivist socio-cultural perspective theory of practical artifacts and guided by a post-positivist paradigm, the authors provided in-service and prospective language teachers in a graduate Applied Linguistics course opportunities to apply relevant theoretical knowledge to their teaching practices in a language learning setting, thereby addressing this gap. The data from this qualitative research are part of the structured journaling assignment in an authentic environment as part of the students’ linguistic practice. The participants were instructed to describe their language learning experience during the linguistic course. The study’s results provide a holistic perspective on investigating the interplay between theory and practice, drawing on participants’ real language learning experiences that shape the development of their teacher identity. The study findings indicate that the participants experienced an increase in their ability to operationalize linguistic theory in applied contexts and link theoretical language teaching concepts to real classroom practices.